A second decade lifetable survival analysis of the Oxford unicompartmental knee arthroplasty. - Price, A; Svard, U (2011)
BACKGROUND: The role of unicompartmental arthroplasty in managing osteoarthritis of the knee remains controversial. The Oxford medial unicompartmental arthroplasty employs a fully congruent mobile bearing intended to reduce wear and increase the lifespan of the implant. Long-term second decade results are required to establish if the design aim can be met. QUESTIONS/PURPOSES: We report the (1) 20-year survivorship for the Oxford mobile bearing medial unicompartmental knee arthroplasty; (2) reasons for the revisions; and (3) time to revision. METHODS: We reviewed a series of 543 patients who underwent 682 medial Oxford meniscal bearing unicompartmental knee arthroplasties performed between 1983 and January 2005. The mean age at implantation was 69.7 years (range, 48-94 years). The median followup was 5.9 years (range, 0.5 to 22 years). One hundred and forty-one patients (172 knees) died. None were lost to followup. The primary outcome was 20-year survival, a key variable in assessing the longevity of arthroplasty. RESULTS: The 16-year all cause revision cumulative survival rate was 91.0% (CI 6.4, 71 at risk) and survival was maintained to 20 years (91.0%, CI 36.2, 14 at risk). There had been 29 revision procedures: 10 for lateral arthrosis, nine for component loosening, five for infection, two bearing dislocations, and three for unexplained pain. In addition, five patients had undergone bearing exchange, four for dislocation and one for bearing fracture. The mean time to revision was 3.3 years (range, 0.3-8.9 years). CONCLUSIONS: Mobile bearing unicompartmental knee arthroplasty is durable during the second decade after implantation. LEVEL OF EVIDENCE: Level IV, therapeutic study. See the Guidelines for Authors for a complete description of levels of evidence.